The Emergence and Spread of Novel SARS-CoV-2 Variants - Yi, Huaimin; Wang, Jin; Wang, Jiong; Lu, Yuying; Zhang, Yali; Peng, Ruihao; Lu, Jiahai; Chen, Zeliang (Frontiers in Public Health, 2021)
Since severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) began to spread in late 2019, laboratories around the world have widely used whole genome sequencing (WGS) to continuously monitor the changes in the viral genes and discovered multiple subtypes or branches evolved from SARS-CoV-2. Recently, several novel SARS-CoV-2 variants have been found to be more transmissible. They may affect the immune response caused by vaccines and natural infections and reduce the sensitivity to neutralizing antibodies. We analyze the distribution characteristics of prevalent SARS-CoV-2 variants and the frequency of mutant sites based on the data available from GISAID and PANGO by R 4.0.2 and ArcGIS 10.2. Our analysis suggests that B.1.1.7, B.1.351, and P.1 are more easily spreading than other variants, and the key mutations of S protein, including N501Y, E484K, and K417N/T, have high mutant frequencies, which may have become the main genotypes for the spread of SARS-CoV-2.